2011
DOI: 10.1007/s11661-011-0872-z
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetics Model for Martensite Transformation in Plain Carbon and Low-Alloyed Steels

Abstract: An empirical martensite kinetics model is proposed that both captures the sigmodial transformation behavior for alloy steels and remains computationally efficient. The model improves on the Koistinen and Marburger model and the van Bohemen and Sietsma model with a function that better represents the transformation rate, especially during the early stages. When compared with existing models, the proposed model exhibits better predictions of volume fraction of martensite. The proposed model also predicts various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 16 publications
(28 reference statements)
1
25
0
5
Order By: Relevance
“…Furthermore, the volume fraction of AM (VAM) can also be calculated by Equations and KBS=0.02240.0107xnormalC0.0007xMn0.00005xNi0.00012xCr0.0001xMo VAM=1exp true[KBS(normalMnormalST)true] where x i represents the mass percent of element “ i ”, T is the austempering temperature, and K BS is a constant.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the volume fraction of AM (VAM) can also be calculated by Equations and KBS=0.02240.0107xnormalC0.0007xMn0.00005xNi0.00012xCr0.0001xMo VAM=1exp true[KBS(normalMnormalST)true] where x i represents the mass percent of element “ i ”, T is the austempering temperature, and K BS is a constant.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of those alloying elements on the kinetics of athermal martensitic transformation was therefore not considered by van Bohemen and Sietsma. Recently, Lee and Van Tyne [15] modified the K-M equation adding two parameters, a and b in Table I, which are composition dependent. They suggested that the actual variation of the martensite formation in alloy steel had a sigmoidal temperature dependence and that their equation captured the correct sigmoidal temperature dependence of the transformation of alloy steels.…”
Section: ½2mentioning
confidence: 99%
“…However, the effect of B on the kinetics of the martensitic transformation has not been studied. In addition, the effects of alloying elements on a, i.e., the kinetics of martensitic transformation, have rarely been reported, and to the best of the authors' knowledge, only the results reported by van Bohemen and Sietsma [14] and Lee et al [15] are currently available for comparison. van Bohemen and Sietsma did not provide an explanation for the sign of the rate parameter a and justification of their results will require further study.…”
Section: ½2mentioning
confidence: 99%
“…The formal description of martensitic transformation kinetics remains an active topic in steel research, now exceeding nearly a century of interest [1][2][3][4][5][6][7][8][9][10][11][12] . The equations predicting this phenomenon invariably contain fitting parameters.…”
Section: Introductionmentioning
confidence: 99%